2011
DOI: 10.1088/0004-637x/728/1/12
|View full text |Cite
|
Sign up to set email alerts
|

The Spin Parameter of Uniformly Rotating Compact Stars

Abstract: We study the dimensionless spin parameter j (= cJ/(GM 2 )) of uniformly rotating neutron stars and quark stars in general relativity. We show numerically that the maximum value of the spin parameter of a neutron star rotating at the Keplerian frequency is j max ∼ 0.7 for a wide class of realistic equations of state. This upper bound is insensitive to the mass of the neutron star if the mass of the star is larger than about 1 M ⊙ . On the other hand, the spin parameter of a quark star modeled by the MIT bag mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 50 publications
5
111
0
1
Order By: Relevance
“…Interestingly, for κ = −1 and N = 3, not only does the first ergoregion solution appear before the point of maximum charge, but it occurs for a spin parameter large than one. High spin parameters, although fairly common for planets and nuclear stars, are quite rare to achieve with compact objects, for instance rapidly rotating neutron stars are usually bound by a * ≤ 0.7, while the more exotic quark stars could go beyond the unit slope [32].…”
Section: B N=3 Modelmentioning
confidence: 99%
“…Interestingly, for κ = −1 and N = 3, not only does the first ergoregion solution appear before the point of maximum charge, but it occurs for a spin parameter large than one. High spin parameters, although fairly common for planets and nuclear stars, are quite rare to achieve with compact objects, for instance rapidly rotating neutron stars are usually bound by a * ≤ 0.7, while the more exotic quark stars could go beyond the unit slope [32].…”
Section: B N=3 Modelmentioning
confidence: 99%
“…The Kerr parameter is important for neutrons stars and in general, compact objects. To be more specific, it can lead to possible limits for the compactness on neutron stars and consequently on the spin frequency, and second, can be a criteria for determining the final fate of the collapse of a rotating compact star [31,42]. The relation which describes the Kerr parameter [31] is…”
Section: Kerr Parametermentioning
confidence: 99%
“…Lo & LIN (2011) has shown that j max ∼ 0.7 for neutron stars without hyperons, while the spin parameter of a quark star modeled by the MIT bag model can be larger than unity and does not have a universal upper bound. It is interesting to further explore what the key factor to determine the spin parameter is, and study the reliability of the result on various selected EOSs of dense matter, such as hyperonic NS and hybrid stars, which are not considered yet in Lo & LIN (2011). The calculations and the results for strange quark stars with the MIT bag model are very similar to those in Lo & LIN (2011), which have j max > 1 for most of star masses, thus we do not exhibit here.…”
Section: The Crust Effects On Dimensionless Spin Parametermentioning
confidence: 99%
“…In Kato (2008), based on a Resonantly Excited Disk-Oscillation Model, they suggested that the observed correlations in Cir X-1 could be well described by adopting M = 1.5 ∼ 2.0M ⊙ and j ∼ 0.8. Thus, Lo & LIN (2011) suggested the central star in Cir X-1 could be a quark star if assuming Kato's model is correct, due to the calculated uniformly rotating neutron stars with hadronic matter cannot have j > 0.7. However, in this work, we show that the j max of the traditional NS, hyperonic NS and hybrid stars are also larger than 0.7 if the crust structure is not included.…”
Section: The Crust Effects On Dimensionless Spin Parametermentioning
confidence: 99%